Determinants of Technological Innovation on the Income of Urban Farming Farmers in the Digital Economy Era - Noor Salim; Darwati Susilastuti; Henita Fajar Oktavia; Safira Fathin (Badan Penerbitan Fakultas Pertanian (BPFP), 2022)
The rapid growth of urbanization in urban areas raises doubts about the future of urban farming. However, urban farming can survive due to the ability of urban farming to innovate in expanding its functions in various factors that hinder it. Farmers as actors need to be empowered with various knowledge and technological innovations. The purpose of the study was to analyze the simultaneous and partial effect of variables on land area, risk-taking courage, farmer's age, and sources of information on technological innovation in urban farming farmers in the digital economy era, what factors are dominant, and analyze the effect of technological innovation on farmers' income—survey research method with OLS Multiple Regression of primary data analysis technique on 70 respondents. The result of the research is that the source of information has a significant effect on technological innovation and is the dominant factor with a value of β =57.6%. In contrast, the variables of land area, risk-taking courage, and age have no effect. Technological innovation has a significant impact on income. The research finding is that technological innovation in urban farming is not influenced by land area, age of farmers, and risk-taking courage but predominantly by sources of information that have implications for farmers' income.